ANALYSIS OF DONISH'S VIEWS ON REFORMING THE EDUCATION AND TRAINING SYSTEM (Scientific journal of the Fergana State University, 2024)
In this article, the author analyzed the views of Ahmad Donish on the ongoing reforms in the education system and upbringing of his era. Expressing his educational and moral views, he relied on the ethical works of Persian-Tajik, Indian, Arab and Greek thinkers of the past